Transformation of Da’wah Communication from the Perspective of Islamic Communication: A Literature Study - Nurrahman Nurrahman; Zeira Salim Ritonga; Gusti Prabowo; Muhammad Syaifur Rozaq; Ahmad Tamrin Sikumbang (KURAS Institute, 2025)
This article analyzes the transformation of Da’wah communication in the digital era from the perspective of Islamic communication. The study is motivated by the rapid shift of Da’wah activities toward digital platforms, which expands the dissemination of Islamic messages but also raises challenges related to religious authority, message commodification, and ethical communication. Despite the increasing presence of digital Da’wah, studies that integrate these developments with the normative principles of Islamic communication remain limited. Therefore, this research aims to examine the patterns of transformation in digital Da’wah and identify the relevance of Islamic communication values in guiding its development. This study employs a qualitative literature review approach. Data were collected from scholarly books and peer-reviewed journal articles published within the last five years that discuss digital Da’wah, Da’wah communication strategies, and Islamic communication principles. The selected literature was analyzed using thematic analysis to identify major patterns, conceptual arguments, and emerging issues. Data verification was conducted through cross-comparison among sources to ensure consistency and reliability. The findings indicate that digital Da’wah transforms communication practices through message visualization, short narratives, and interactive storytelling that encourage two-way engagement between da'i and mad'u. While digital media broadens the reach and inclusivity of Da’wah, it also introduces risks of shifting authority and commercialization of religious content. This study contributes by proposing the reinforcement of Islamic communication values qawlan sadīdan, qawlan balīghan, qawlan ma‘rūfan, and qawlan layyinan as an ethical framework for adaptive and socially transformative digital Da’wah